The integration process of the retornados in Portugal (1975-2018) : comparative analysis with the french case of the pieds-noirs from Algeria - (:unkn) unknown (My University, 2020)
After the Carnation Revolution of April 25th 1974, which put an end to the Estado Novo regime in place in Portugal since 1926, the democratization process, and simultaneously the decolonisation process of the African territories under Portuguese rule, began. One of the consequences of the end of Portuguese empire in Africa, was the arrival and settlement in Portugal of nearly half-a-million Portuguese ex-colonists, coming mostly from Angola and Mozambique. Known as retornados, or returnees, most of them arrived during the summer of 1975, and represented 5% of the Portuguese resident population. In a context of high political and social instability, and of a global economic crisis, this migratory phenomenon represented an additional challenge for the Portuguese administration that had to devise and implement measures in order to welcome, accommodate, and integrate those national migrants into the Portuguese economy and society. This study focuses on the integration process of this population, in a comparative perspective with the French case of the pieds-noirs from Algeria, repatriated during the process of the Algerian independence.
Keywords: African Research